Discovery of novel coffee diterpenoids with inhibitions on Cav3.1 low voltage-gated Ca2+ channel. (15th May 2022) - Hu, Guilin; Dong, Ding; Du, Shuzong; Peng, Xingrong; Wu, Mingkun; Shi, Qiangqiang; Hu, Kun; Hong, Defu; Wang, Xiaoyuan; Zhou, Lin; Nian, Yin; Qiu, Minghua
Graphical abstract: Highlights: Diterpenoids including three kinds of rare skeletons were identified. Diterpenoids with notable Cav 3.1 inhibitory activities were initially discovered. The ring at C-18 and C-19, and esterification of OH-17 with long-chain are the key features for Cav 3.1 inhibition. Abstract: Seven new (1 –4, 6 –8 ) diterpenoids with rare skeletons and seven known ones (9, 12, 17, 18 and 23 –25 ) were isolated from roasted beans of Coffea arabica L . Together with previously obtained diterpenoids, a total of 26 molecules (1 –25, 4a ) were evaluated their activities on Cav 3.1 low voltage-gated Ca 2+ channel. Compounds 1, 3, 6, 7, 12, 13, 17, 19 and 24 exhibited noticeable Cav 3.1 inhibitions (41.2%-96.1%) at 10 μM. The IC50 values of 1, 6, 7, 12, 13, 17 and 24 are 2.9, 2.3, 0.68, 14.8, 11.6, 6.1 and 6.8 μM, respectively. The ring moiety at C-18 and C-19, and esterification of OH-17 with long-chain fatty acids seem important for their activities. Further studies indicated that 1 and cafestol may act on different binding sits with the Cav 3.1 blocker Z944, which is in clinical trial. Significantly, the present study initially shows that coffee diterpenoids are potential natural resources for Cav 3.1 inhibitors.